Pendidikan Islam Berbasis Multikultural di Indonesia: Analisis Pemikiran Azyumardi Azra dan James A. Banks - Priska Nurullah Sa’ada; Nurul Humaidi (Civiliza Publishing, Indonesia., 2026)
Indonesia as a multicultural nation, faces increasingly complex challenges in fostering a harmonious society amid its diverse religious, ethnic, cultural, and linguistic backgrounds. In this context, Islamic education is expected not only to promote individual piety but also to cultivate the values of tolerance, justice, equality, dialogue, and respect for diversity. This article aims to describe and analyze Azyumardi Azra’s perspective on multicultural Islamic education in Indonesia and to compare it with the concept of multicultural education developed by James A. Banks. This study employed a qualitative approach using a library research method, while the data were analyzed through content analysis of the primary works of both scholars, supported by relevant academic literature. The findings reveal that Azyumardi Azra views multicultural Islamic education as a strategic instrument for strengthening national integration through the internalization of moderate, inclusive, democratic, and nationally oriented Islamic values (Azra, 2003, 2019); (Idris, 2020) Meanwhile, James A. Banks emphasizes that multicultural education should be implemented through curriculum reform, equitable pedagogy, prejudice reduction, the empowerment of school culture, and the promotion of social justice, thereby ensuring equal educational opportunities for all students regardless of their backgrounds (J. A. Banks, 2016; J. A. Banks & Banks, 2019). The analysis further demonstrates that, despite their different epistemological foundations, both scholars converge on the view that education serves as a transformative medium for fostering respect for diversity and developing democratic citizens. Their ideas provide a robust conceptual foundation for the development of Islamic education in Indonesia by integrating Islamic values with the principles of multiculturalism, thereby strengthening social cohesion and preserving national unity within a pluralistic society.